Iron and Iron Oxide Nanoparticles Synthesized Using Green Tea Extract: Improved Ecotoxicological Profile and Ability to Degrade Malachite Green - Plachtová, Pavla; Medříková, Zdenka; Zbořil, Radek; Tuček, Jiří; Varma, Rajender S; Maršálek, Blahoslav (ACS sustainable chemistry & engineering, 2018)
In recent years, iron-based nanoparticles (FeNPs) have been successfully used in environmental remediation and water treatment. This study examined ecotoxicity of two FeNPs produced by green tea extract (smGT, GTFe) and their ability to degrade malachite green (MG). Their physicochemical properties were assessed using transmission electron microscopy, X-ray powder diffraction, dynamic light scattering, and transmission Mössbauer spectroscopy. Using a battery of ecotoxicological bioassays, we determined toxicity for nine different organisms, including bacteria, cyanobacterium, algae, plants, and crustaceans. GTFe, amorphous complex of Fe(II, III) ions and polyphenols from green tea extract, proved low capacity to degrade MG and was toxic to all tested organisms. Superparamagnetic iron oxide NPs (smGT) derived from GTFe, showed no toxic effect on most of the tested organisms up to a concentration of 1g/L, except for algae and cyanobacterium and removed 93 % MG at concentration 125 mg Fe/L after 60 minutes. The procedure described in this paper generates new superparamagnetic iron oxide NPs from existing and toxic GTFe, which are nontoxic and has degradative potential for organic compounds. These findings suggest low ecotoxicological risks and suitability of this green-synthesized FeNPs for environmental remediation purposes.
Keywords: Green tea; Malachite green; Ecotoxicity; Iron nanoparticles; Remediation